Global Mobile Media. (Taylor & Francis, 2010)
There are now over one and a half billion mobile phones used worldwide. Alongside phones, there are a range of other portable media devices widely used including analogue and digital radio receivers, portable music players (MP3 players and iPods), laptop computers, not to mention a wider field of mobile technologies, including wearable computers, positioning and sensing technologies, and Radio Frequency Identification (RFID) devices. ""Global Mobile Media"" sets out to integrate an understanding of the mobile media economy (political and cultural), with knowledge of mobile culture (new media f.